2022
DOI: 10.3389/fpls.2022.853326
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Transcriptome and Metabolome Profiles Reveal Common and Unique Pathways Involved in Seed Initial Imbibition Under Artificial and Natural Salt Stresses During Germination of Halophyte Quinoa

Abstract: Salt stress is a major environmental factor that seriously restricts quinoa seed germination. However, the key regulatory mechanisms underlying the effect of salt stress on the initial imbibition stage of quinoa seeds are unclear. In this study, dry seeds (0 h) and imbibed (8 h) seeds with 450 mM NaCl (artificial salt) and 100% brackish water of Yellow River Estuary (BW, natural salt) were used to assess the key salt responses based on germination, transcriptome, and metabolome analyses. The results indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…The taxa of Acidobacteriales, Bacillus, Micromonosporaceae, Nitrospira, and Ellin6067 activate and significantly enrich galactose metabolism, fructose and mannose metabolism, lysine degradation metabolism, and BCAA metabolism through interactions at stages of radicle protrusion and elongation. The enrichment of more carbohydrate metabolic pathways indicates that the increase in the contents of sugar and amino acid at the early stage of germination plays a vital role in promoting the germination of O. henryi seeds, which is consistent with data obtained by Zhao et al and Yan et al [46,47]. Lysine can directly enter the TCA cycle through catabolism, and its degradation helps to maintain mitochondrial respiration under carbon-limited conditions during aging [48].…”
Section: Metabolic Pathways Activated By Spermosphere Bacteria Involv...supporting
confidence: 90%
“…The taxa of Acidobacteriales, Bacillus, Micromonosporaceae, Nitrospira, and Ellin6067 activate and significantly enrich galactose metabolism, fructose and mannose metabolism, lysine degradation metabolism, and BCAA metabolism through interactions at stages of radicle protrusion and elongation. The enrichment of more carbohydrate metabolic pathways indicates that the increase in the contents of sugar and amino acid at the early stage of germination plays a vital role in promoting the germination of O. henryi seeds, which is consistent with data obtained by Zhao et al and Yan et al [46,47]. Lysine can directly enter the TCA cycle through catabolism, and its degradation helps to maintain mitochondrial respiration under carbon-limited conditions during aging [48].…”
Section: Metabolic Pathways Activated By Spermosphere Bacteria Involv...supporting
confidence: 90%
“…Salt stress is an abiotic stress that severely inhibits the growth, development, and productivity of numerous agricultural crops, especially during the early stages of development [ 2 , 3 , 14 , 30 ]. Crop plants have developed a range of strategies in response to the increasing concentration of Na + and Cl - ions in soil [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2022) showed that amino sugar and nucleotide sugar metabolism was one of the pathways most significantly enriched in pecan plants under salinity stress. By integrating transcriptome and metabolome profiles of mature and plump quinoa seeds imbibed under salinity stress in the dark for 8.0 h, Yan et al. (2022) showed that the amino sugar and nucleotide sugar metabolism significantly enriched.…”
Section: Discussionmentioning
confidence: 99%
“…Using physiological, proteomic, and metabolomic methods to study salt tolerance in pecans, Jiao et al (2022) showed that amino sugar and nucleotide sugar metabolism was one of the pathways most significantly enriched in pecan plants under salinity stress. By integrating transcriptome and metabolome profiles of mature and plump quinoa seeds imbibed under salinity stress in the dark for 8.0 h, Yan et al (2022) showed that the amino sugar and nucleotide sugar metabolism significantly enriched. In the present study, this pathway was enriched mainly in the leaves, where all enzymes differentially expressed were regulated positively-present in the leaves of stressed plants but not in the leaves of control plants.…”
Section: Discussionmentioning
confidence: 99%